PENGARUH KECERDASAN EMOSIONAL DAN MINAT BELAJAR TERHADAP PEMAHAMAN AKUNTANSI PADA MAHASISWA PROGRAM STUDI AKUNTANSI DI UNIVERSITAS MEDAN AREA - Mohd. Idris Dalimunthe (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
This study aims to determine how much impact from emotional intelligence and interest in learning towards students' accounting understanding Medan Area University, batch 2015 - 2019. Population of this study totaled 631 students of accounting classes in the morning and evening who were the source of the data secondary comes from the academic staff of the Medan Area University. sample inside This study amounted to 88 students who had been deliberately selected based on the criteria set by the researcher, then processed using multiple linear regression and measured using a Likert scale for his own revolutionary. The results of this study indicate that Emotional Intelligence and Interest in Learning has a significant effect on Accounting Comprehension, both partial or simultaneous. This is evidenced by the partial significance figures for emotional intelligence itself 0.015 and for interest in learning 0,000 where both numbers are less than 0.05. simultaneously emotional intelligence and interest in learning has a significant effect on accounting understanding students are proven with a significance value of 0.000 which is also smaller from 0.05.